Near‐Infrared Light‐Emitting Diodes from Organic Radicals with Charge Control - Emrys Evans (Advanced Optical Materials, 2022)
Organic radicals with fluorescence from doublet-spin energy manifolds circumvent efficiency limits from singlet–triplet photophysics in organic light-emitting diodes (OLEDs). The singly occupied molecular orbital (SOMO) in radicals enables the higher potential performance. The SOMO also presents substantially lower energy frontier orbitals compared to conventional fluorescent emitters for device operation, which can cause severe electron trapping that limits the performance of radical OLEDs. To improve optoelectronic performance, electron donor–acceptor-mixed hosts are used to control charge transport for enhanced radical electroluminescence by charge recombination on SOMO and frontier orbitals. The (2-chloro-3-pyridyl)bis(2,4,6-trichlorophenyl)methyl-based radical is designed to test the charge-controlled device architectures in OLEDs by transient analysis and device characterization studies. Efficient radical OLEDs with 4.7% maximum external quantum efficiency are reported—showing substantial advances in performance for OLEDs with peak emission beyond 800 nm. In addition, substantially improved performance at higher current density operation and more than two orders of higher lifetime stability are achieved with mixed hosts. These results enable pathways to infrared-emitting devices with applications ranging from communications to bioimaging.